Moral expressivism and sentential negation - Sinclair, Neil (Springer, 2011)
This paper advances three necessary conditions on a successful account of sentential negation. First, the ability to explain the constancy of sentential meaning across negated and unnegated contexts (the Fregean Condition). Second, the ability to explain why sentences and their negations are inconsistent, and inconsistent in virtue of the meaning of negation (the Semantic Condition). Third, the ability of the account to generalize regardless of the topic of the negated sentence (the Generality Condition). The paper discusses three accounts of negation available to moral expressivists. The first – the ‘dominant commitment account’ – fails to meet the Fregean Condition. The two remaining accounts – one suggested by commitment semantics and the other by recent analyses of the ‘expression’ relation – satisfy all three conditions. Mark Schroeder’s argument that the dominant commitment account is the only option available to expressivists is considered and rejected.